ANALISIS KETERBACAAN BUKU DWIBAHASA SERI MENGENAL HEWAN: CERITA SI LABA-LABA - Arif Hidayat (Wanastra: Jurnal Bahasa dan Sastra, 2014)
Nowadays, there are many books aimed for children who are set as interesting as possible to attract and develop their reading skill as well as to give sources of knowledge and science. Usually, the attraction given is in the form of full picture and easy reading book which is specially made for children as beginner reader.. One of this kind of books is Seri Mengenal Hewan: Cerita Si Laba-laba which is a bilingual book specially made to attract as well as introduce English to the childre. However, does it really use a suitable language for children so that they are not easily bored because of the complexity of the language used? In this study, using Fry Formula and Graphic, and by analyzing the linguistics usage level and cultural side scoring column, the writer found that the readability of the source text (Bahasa Indonesia) is not suitable for children below sixth gradegrade level of elementary school. Meanwhile, the readability in the target text is more suitable for children-but not less than the third grade level. However, the translation (English parts) needs some revision. After reading this study, hopefully the readers can be more careful in choosing bilingual books which have good readabilityquality.